A química de tintas e revestimentos anti-incrustrantes para a indústria naval - Moraes, Juliana Rafael de (Universidade Federal de São Carlos, 2022)
This Final Paper makes a brief review of the main A/F paints and coatings for ships and vessels, the main protection material against marine biofouling that affects world trade as a whole. Different types of A/F paints have been developed and improved over the years, the first protection techniques originated from ancient peoples such as the Phoenicians, using natural oils and resins mixed with antifouling agents. The complexity of the marine environment and the processes that make up biofouling have led to these coatings being improved. Modernly, the protection of vessels started to consist of systems based on synthetic polymeric matrices, such as self-polishing paints with biocides derived from organotin compounds that revolutionized the industry in this segment. However, the concern with the environment brought new challenges to the market, when in 2003 the use of organotin agents, the most used agent in the formulations of paints and A/F coatings, was banned, due to the irreparable environmental damage caused by these compounds. Nowadays, the search for new coating technologies that address different effective protection mechanisms and biocidal agents that are less harmful to the environment are topics of research worldwide
The chemistry of antifouling paints and coatings for shipbuilding
Keywords: Tintas e revestimentos; Indústria naval; Polímeros; Antiincrustração; Paints and coatings; Shipbuilding; Polymers; Antifouling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS